(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research paper explores Emily Dickinson’s role as a rebellious figure in the context of mid-19th century American poetry. The paper highlights how Dickinson challenged patriarchal norms and subverted traditional expectations for women’s writing. It draws parallels between Dickinson and other women writers like Elizabeth Barrett Browning, Christina Rossetti, and George Eliot, who challenged societal limitations. The paper delves into Dickinson’s struggle against the male-dominated literary hierarchy, her unique themes, and her defiance of societal norms. It discusses her reclusive lifestyle as a way to escape societal constraints and examines how her poetry became a vehicle to challenge repression and silence experienced by women. The paper underscores Dickinson’s influence on later generations of women writers, such as Adrienne Rich, Sylvia Plath, and Marianne Moore. It also highlights the rediscovery of Dickinson’s work by feminist critics in the mid-20th century, emphasizing her contribution to the female literary tradition. Overall, the research emphasizes Dickinson’s legacy as an empowering figure who defied patriarchal norms and continues to inspire women writers to challenge male-dominated literary landscapes.